Is Transparency a Free Lunch? Evidence from the Italian Local Health Authorities - Paolo Lorenzo Ferrara; Calogero Guccio; Carla Scaglioni (ZBW - Leibniz Information Centre for Economics, 2021)
The healthcare sector is often considered one of the most prone to corruption and transparency policies have been proposed in several countries to fight bribery and corruption. Indeed, the transparency of public bodies potentially play a relevant role in preventing misbehaviours and favouring accountability. The paper contributes to the broader understanding of the transparency role in the healthcare sector using Italy as a case study. For this purpose we first build a composite indicator of transparency, already proposed in the literature in the field, to assess the differences in transparency and integrity between Italian Local Health Authorities (LHAs). Then we use multivariate regression to explore the relationship between the performance for different expenditure functions at LHAs level and transparency index. Our results show a wide difference in transparency and integrity among LHAs that does not always follow the classic north-south divide in the country. In addition, we find results consistent with the idea that transparency is generally associated with better performance of the LHAs in containment total health expenditure while imposing larger administrative burdens.
Keywords: C92; H30; H41; 330; Transparency; Administrative burdens; Accountability; Local Health Authorities; Italian NHS